Reconstructing Baseline Data for Impact Evaluation and Results Measurement - Bamberger, Michael (World Bank, Washington, DC, 2012)
Many international development agencies and some national governments base future budget planning and policy decisions on a systematic assessment of the projects and programs in which they have already invested. Results are assessed through Mid-Term Reviews (MTRs), Implementation Completion Reports (ICRs), or through more rigorous impact evaluations (IE), all of which require the collection of baseline data before the project or program begins. The baseline is compared with the MTR, ICR, or the posttest IE measurement to estimate changes in the indicators used to measure performance, outcomes, or impacts. However, it is often the case that a baseline study is not conducted, seriously limiting the possibility of producing a rigorous assessment of project outcomes and impacts. This note discusses the reasons why baseline studies are often not conducted, even when they are included in the project design and funds have been approved, and describe strategies that can be used to 'reconstruct' baseline data at a later stage in the project or program cycle.